Access denied: the challenges of technology use for children with special needs / Sri Yusmawati Mohd Yunus ... [et al.]. - Mohd Yunus, Sri Yusmawati; Aziz Fadzillah, Nor Azlina; Yusof, Rozianiwati; Abdul Rahman, Normaziah; Hashim, Norhafizah (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2025)
Children with special abilities can refer to a wide range of talents, skills or developmental differences that distinguish them from other normal kids. These capabilities can be intellectual, creative or physical, and sometimes are connected with situations or exceptional traits like gifted children, children with learning disabilities but exceptional skills like dyslexia, ADHD or autism, children with savant syndrome, children with physical abilities and children with Autism Spectrum Disorder (ASD) and special skills. Supporting children with special abilities requires recognizing and nurturing their strengths while helping in areas where they might face challenges. By using technology, it can greatly assist children with special abilities by offering tools and resources that enhance their learning, development and independence. Whether they are gifted, have learning differences, or possess specific talents, technology can provide tailored solutions that align with their needs.